Kegiatan Bakti Sosial Layanan Pemeriksaan Kesehatan dan Terapi Komplementer Bekam Gratis di Desa Kandangrejo, Kecamatan Brati, Kabupaten Grobogan - Wahyu Riniasih; Silvi Nur Hakiki; Rosandra Firdi Silvian; Nalfriza Alfianti; Deny Rahmat; Anik Wahyunita; Wahyu Dewi Hapsari; Mingle A Pistanty; Suryani; Sutiyono; Ricard Janottama (LPPM AN Nuur, 2023)
Background:One of the responsibilities of nurses in dealing with health problems is with maximum prevention where a nurse or health worker provides education and health checks to the community regarding the importance of maintaining health from an early age. Purpose: of carrying out this community service is to play an important role in improving health status in the community where this examination can prevent disease, especially in the residents of Kandangrejo village. Method :uses health counseling actions related to degenerative diseases, assessments, health checks in the form of checking blood pressure, sugar levels and uric acid. Where this also ended with the complementary implementation of cupping in treating residents' complaints related to the illness they were experiencing. This activity lasted for 1 full day which was attended by the local RT/RW on April 3 2023. The results: obtained in the community service activities were that the people of Kandangrejo village became aware of their health conditions and could feel the effects of complementary cupping therapy after the action was taken .